Video-Driven Multimedia, Web-Based Training in the Corporate Sector: Pedagogical Equivalence and Component Effectiveness - Pang, Katherine (International Review of Research in Open and Distributed Learning, 2009)
The purpose of this study was to assess the pedagogical equivalence, as determined by knowledge gains, and the pedagogical effectiveness of certain components in a video-driven multimedia, web-based professional development training program as compared to a traditional, face-to-face program under real-world constraints of time and limited economic resources. The study focused on the use of video-driven multimedia, web-based instruction in the corporate environment to determine if the quality of the learning experience and the knowledge gained from the instruction were the same as with traditional methods. This experimental study assigned business professionals quasi-randomly to either a control group or an experimental group, where they attended either a live-instructed professional development program or a video-driven multimedia, web-based professional development program. Overall, results indicated that the video-driven multimedia, web-based instruction was not only pedagogically equivalent in terms of knowledge gains to the live instruction but that the knowledge gains were slightly higher among the web-based participants. Further, certain components in the web-based environment contributed more than components in the live environment to pedagogical effectiveness.